2017
DOI: 10.3389/fphar.2017.00902
|View full text |Cite
|
Sign up to set email alerts
|

HDAC2 and HDAC5 Up-Regulations Modulate Survivin and miR-125a-5p Expressions and Promote Hormone Therapy Resistance in Estrogen Receptor Positive Breast Cancer Cells

Abstract: Intrinsic or acquired resistance to hormone therapy is frequently reported in estrogen receptor positive (ER+) breast cancer patients. Even though dysregulations of histone deacetylases (HDACs) are known to promote cancer cells survival, the role of different HDACs in the induction of hormone therapy resistance in ER+ breast cancer remains unclear. Survivin is a well-known pro-tumor survival molecule and miR-125a-5p is a recently discovered tumor suppressor. In this study, we found that ER+, hormone-independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 57 publications
0
48
0
Order By: Relevance
“…It has been demonstrated that the epigenetic modulators could modulate the miR‐125‐5p expression,13, 25, 26 and its promoter is hypermethylated in glioma cells 27. We analysed the miR‐125a‐5p methylation status in gastric cancer tissues and adjacent non‐tumour tissues.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that the epigenetic modulators could modulate the miR‐125‐5p expression,13, 25, 26 and its promoter is hypermethylated in glioma cells 27. We analysed the miR‐125a‐5p methylation status in gastric cancer tissues and adjacent non‐tumour tissues.…”
Section: Resultsmentioning
confidence: 99%
“…These data showed that overexpressing Furthermore, miR-125a-5p has been validated to prevent the cancer cell progression. [10][11][12][13][14][15][16][17][18][19]23,24 However, the underlying mechanism of the low expression of miR-125a-5p in gastric cancer remains unknown.…”
Section: Overexpressing Mir-125a-5p Suppresses Gastric Cancer Develmentioning
confidence: 99%
See 2 more Smart Citations
“…It is highly expressed in embryonic tissues (e.g. neuronal precursor cells and embryonic fibroblasts) and tumors (including both cancer cells and cancer stem cells), and its expression is associated with tumor cell differentiation, proliferation, invasion, and metastasis [3][4][5][6][7][8][9][10][11]. Interestingly, a few studies revealed that BIRC5 also plays an important role in neural cell proliferation after traumatic brain injury and in cardiomyocytes survival maintenance after cardiac injury [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%